2019
DOI: 10.1093/jncics/pkz040
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Survival Among Young Women With Stage I–III Breast Cancer: SEER 2000–2015

Abstract: Background Although recent findings suggest that de novo stage IV breast cancer is increasing in premenopausal women in the United States, contemporary incidence and survival data are lacking for stage I–III cancer. Methods Women aged 20–29 (n = 3826), 30–39 (n = 34 585), and 40–49 (n = 126 552) years who were diagnosed with stage I–III breast cancer from 2000 to 2015 were identified from the Surveillance, Epidemiology, and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 49 publications
2
59
2
3
Order By: Relevance
“…Missing data on molecular subtype were more common in Hispanic women overall and women aged 70 to 84 years in each race/ethnic group (eTable in the Supplement ). 5 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Missing data on molecular subtype were more common in Hispanic women overall and women aged 70 to 84 years in each race/ethnic group (eTable in the Supplement ). 5 …”
Section: Resultsmentioning
confidence: 99%
“…Population-based studies suggest a mostly stable trend in overall breast cancer incidence rates, 1 , 2 although there are documented differences in trends by age at diagnosis and racial/ethnic groups. 1 , 3 , 4 , 5 Moreover, studies have reported racial/ethnic differences in the incidence rates of breast cancer subtypes, defined according to hormone receptor status or ERBB2 (formerly HER2) receptor status, but these studies have mostly considered few broad molecular subtype, race/ethnicity, or age categories. 6 , 7 , 8 A 2019 report 2 of temporal changes in breast cancer incidence rates from 2004 through 2016, which used only breast cancer subtypes by hormone receptor status, found that incidence rates increased for hormone receptor–positive breast cancers (corresponding to both luminal A and B molecular breast cancer subtypes) for all races/ethnicities, although rates began to stabilized after 2011 for non-Hispanic Black and American Indian and Alaska Native women.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the common female tumor [1] and sensitive to chemotherapeutic agent. Among the agents, 5-FU was widely used for the treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid spread of breast cancer and the inability to accurately diagnose and recognize its presence represents a challenge for researchers and developers in biomedical engineering [2]. This challenge leads to deploying new data mining techniques.…”
Section: Introductionmentioning
confidence: 99%